STRATEGI PENINGKATAN MUTU JASA LAYANAN PENDIDIKAN DI PERGURUAN TINGGI - Putri, Hesi Eka (jurnal ekonomi, 2008)
Analysis about strategy development of higher aducation service represent the part of analysis about development of inwrought quality management in college. Analysis about higher aducation service is important because its related to management concept from a sertificable college. Evaluation to quality to college not only done by The Bureau of Accreditation National Collage (BAN-PT), but also by hte own college. Because, as service organization in educational, the college should evaluated to the design of service has been given. Evaluation of quality of service in collage can be conducted with performance's assessment of aspects quality of service. To evaluated performance of aspect quality of service done by comparating a student expectation and perception to design of service that collage offering. It also can be done by the collage by using the SWOT analysis. Its target is to see weakness and strenght from design of service which have walked during the time. From the result assessment to aspect qualit of service, can be formulated a strategy to the make-up of quality of education service.